A Century of Confusion: The Brick Reliefs of Cambodia's Phnom Trap Towers - Green, Phillip Scott Ellis (Journal of the International Association of Buddhist Studies, 2017)
This article reexamines the iconography present at three tenth-century towers located in eastern Cambodia at Phnom Trap and argues that the figures depicted on the inner brick reliefs of the three towers are Buddhist, not Vaiṣṇava or Śaiva as described in early surveys of the site and never challenged. By establishing the Buddhist orientation of this site, my work demonstrates that tenth-century forms of Buddhism in Cambodia involving worship of figures such as Lokeśvara and Vajrapāṇi were more widespread than previously acknowledged in various historical reconstructions of the region.